- #1

- 154

- 2

## Main Question or Discussion Point

I need to derive the solution for the differential equation analytically:

y'' + g(t,y(t)) = 0

y'(0) = z_o

y(0) = y_o

I know the solution is:

y(t) = y_o + z_ot - single integral from 0 to t of (t-s)g(s,y(s))ds

I believe I need to assume something about the solution being a function of e^at somehow due to no damping, but I'm not sure.

y'' + g(t,y(t)) = 0

y'(0) = z_o

y(0) = y_o

I know the solution is:

y(t) = y_o + z_ot - single integral from 0 to t of (t-s)g(s,y(s))ds

I believe I need to assume something about the solution being a function of e^at somehow due to no damping, but I'm not sure.